CONCEPTS AND DIFFERENCES OF DZAWIL FURUDH AND DZAWIL ARHAM IN ISLAMIC INHERITANCE - Badrah Uyuni; Mohammad Adnan (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2023)
The inheritance system is one of the causes or reasons for the transfer of ownership, namely the transfer of property and material rights from the inheriting party, after the death of the person concerned to the recipient of the inheritance by way of replacement based on shara' law. In the rules of inheritance, heirs like blood are divided into three groups, namely: dzawil furudh, ashobah and dzawil arham. In this article we discuss the concept and differences between dzawil furudh and dzawil arham. By using library research as a source of data.